The Silent Catalysts: How Engagement in Blended Learning Shapes Science Students’ Critical Thinking - Jovita Ridhani; Fatma Sukmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Blended learning becomes a central post-pandemic instructional model and understanding how learners engage within these environments is important for enhancing higher-order thinking skill. This study examines the extent to which students’ blended learning engagement predicts the critical thinking skills of high school science students, and whether socioeconomic status (SES) moderates this relationship. A quantitative correlational design was employed, involving 469 science students from Indonesian high schools that have consistently implemented blended learning. Data were collected through a 4-point Likert-scale questionnaire and analyzed using Spearman’s rank-order correlation and bootstrap regression. The results indicated that cognitive engagement was the strongest predictor of critical thinking (ρ = .793, p < .001; β = .751, p < .001), while emotional engagement had a positive but smaller effect (ρ = .291, p < .001; β = .066, p = .029), and behavioral engagement was insignificant (ρ ≈ .000, p = .998; β = –.028, p = .326). Simultaneously, the three dimensions of engagement explained 59.9% of the variability in critical thinking, with no significant moderating effect of SES. However, split-group correlations indicated that the correlation between blended learning engagement and critical thinking was stronger among students from low- (ρ = .512) and high- (ρ = .481) SES groups compared to those from the middle group (ρ = .386), indicating variation in effect magnitude but not direction, thereby clarifying the apparent contradiction with the non-significant moderation test. These findings confirmed cognitive engagement as the core component of reflective learning in blended learning, as well as highlighted the need for instructional designs that strengthen metacognitive regulation and epistemic autonomy for diverse learners.